FAKTOR – FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN RETAILING YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Safira, Aprilia Gita Wulan; Saputro, Dian Festiana Hadi; Isthika, Wikan; Prajanto, Agung (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The aim of this research is to examine and analyze the factors that influence capital structure. The independent variables in this research are Profitability, Liquidity, Company Size and Asset Structure. The subjects of this research are retail companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique in this research was purposive sampling and 14 company samples were taken over a period of 4 years to obtain 56 company samples. The analytical method used in this research is multiple linear regression. The results of this research simultaneously show that profitability, liquidity, company size and asset structure have a simultaneous effect on capital structure. The partial research results show that liquidity and asset structure have an effect on capital structure, while profitability and company size have no effect on capital structure.